Terapi Komplementer Sensory Therapies Movement Untuk Mengurangi Nyeri: Literature Review - Mawar Eka Putri (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Pain is the main complaint most often expressed by sufferers and is the most common reason for seeking and getting medical help. Complementary therapy has recently become the center of attention of many countries, this is because of the holistic philosophy of complementary therapy which means harmony within oneself and health promotion in complementary therapy. This article aims to identify complementary sensory therapies movement to reduce pain. The method used in making this article is critical review. Articles were collected through the Medline database, Google Scholar, Science Direct, Pubmed using keywords: pain, complementary therapy, sensory therapies. The articles selected are those that meet the criteria based on PICO, are published in the range 2009-2019, and in English and Indonesian. The article is then evaluated using the critical appraisal and PRISMA guidelines. Based on the evaluation, there are 6 (six) articles that fit the purpose and review criteria. Aromatherapy and music therapy affect the decrease in pain intensity in patients characterized by a decrease in the average value of pain intensity before and after aromatherapy and music therapy are given. Keywords: Pain, Complementary Therapy, Sensory Therapy